2017
DOI: 10.1007/s11629-016-4096-y
|View full text |Cite|
|
Sign up to set email alerts
|

Age-related changes of leaf traits and stoichiometry in an alpine shrub (Rhododendron agglutinatum) along altitudinal gradient

Abstract: 107leaves and indicated that a high possibility of N limitation in this region. We also concluded that younger leaves could be more sensitive to climate changes due to a greater altitudinal influence on the leaf traits in younger leaves than those in elder leaves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…The stoichiometric properties of carbon, nitrogen, and phosphorus in leaves can reflect plant adaptation strategies to habitats and patterns of nitrogen and phosphorus nutrient limitation (Wardle et al, 2004). Carbon-to-nitrogen and carbon- to-phosphorus ratios reflect the efficiency of nutrient uptake and utilization by plants (Wang et al, 2017). In this study, we found that the leaf carbon-to-nitrogen and carbon-to-phosphorus ratios of the three plant life forms decreased significantly with altitude.…”
Section: Characteristics Of Carbon Nitrogen and Phosphorus Distributi...mentioning
confidence: 53%
“…The stoichiometric properties of carbon, nitrogen, and phosphorus in leaves can reflect plant adaptation strategies to habitats and patterns of nitrogen and phosphorus nutrient limitation (Wardle et al, 2004). Carbon-to-nitrogen and carbon- to-phosphorus ratios reflect the efficiency of nutrient uptake and utilization by plants (Wang et al, 2017). In this study, we found that the leaf carbon-to-nitrogen and carbon-to-phosphorus ratios of the three plant life forms decreased significantly with altitude.…”
Section: Characteristics Of Carbon Nitrogen and Phosphorus Distributi...mentioning
confidence: 53%
“…Compared with trees at low elevation in this study, the trees at high elevation did not show higher concentrations of NSC and greater increases in NSC in winter, suggesting that the freezing point depression for C. gracilis by accumulating sugars is not a main way of achieving low temperature resistance and the individuals at upper limit must employ other strategies to adapt to colder winter temperature and longer duration of winter (Körner, 2012). Elsewhere, leaves of species at higher elevation tend to have higher LMA to enhance the adaptability with low temperature (Ball et al, 2002; Wang et al, 2017). Indeed, LMA of C. gracilis also significantly increased with decreasing temperature in the current study—as has been found in previous studies at intraspecific scales (González‐Zurdo, Escudero, Babiano, García‐Ciudad, & Mediavilla, 2016; Read et al, 2014; Vitousek et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…The phenotypic differentiation of leaf features can be strongly influenced by the environment [34]. The variability and complexity of environmental factors may be the main contributors to the conservative phenotypic variance of Betula albosinensis, which has long lived at low temperatures and high light exposure.…”
Section: Trade-offs Between Leaf Anatomical Traitsmentioning
confidence: 99%